Sejarah Perkembangan Dan Peranan Tv Berbasis Dakwah Islam - Erwan Efendi; Fakhrul Febrian Hasugian; Lia Agustina (Peneliti.net, 2023)
As a communication medium, television can play its role as an interesting channel to convey good messages to society. Including religious messages which are usually called da'wah. In order to convey da'wah messages in the modern era, as it is now, it has become imperative for preachers to utilize all available technology to make it easier to achieve the goals of da'wah and the goals of da'wah. Without utilizing existing media, the da'wah process will run slowly. Therefore, da'wah organizers must be wise in placing media that can support it